Aesthetics, Violence, and Indigeneity. - Rickard, Jolene (Public, 2016)
This essay considers the intersectionality between the field of art history focused on the subject category of Native American or Indigenous art and Indigenous Studies. Methodological gaps in the field of art history are discussed through the canonical genre of landscape art with a comparative reference to key exhibitions; Land Spirit Power: First Nations at the National Gallery of Canada, (1992), The West As America: Reinterpreting Images of the Frontier, 1820-1920, (1991), Submuloc Show/Columbus Wohs (1992), Our Land/Ourselves: Contemporary Native American Landscape (1991) and Picturing the Americas: Landscape Painting from Tierra del Fuego to the Artic (2015). The aestheticization of the colonization of the Americas as represented in the genre of landscape art is interrogated as a form of historical violence that needs to be decolonized within the field of art history.
OCLC: 1051992463
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé